Atividades biológicas in vitro do extrato pigmentado de Talaromyces marneffei isolado de ambiente marinho - RODRIGUES , Igor Vinícius Pimentel (2019)
Introduction: Talaromyces marneffei is an emerging pathogenic fungus responsible for causing fatal mycosis mainly in immunocompromised individuals. The fungi belonging to the genus Talaromyces have different ascomas, usually yellow, white, cream, rosy or reddish, in which ascospores are found, which produce varied pigments, among them the red pigmentation used in this work. These microorganisms have been gaining increasing prominence in the pharmaceutical industry because of their ability to provide antibiotics, immunosuppressants, enzymes and anti-cancer drugs. Aims: To evaluate the in vitro antifungal and antibacterial activities of the intracellular red pigmented extract (IRPE) produced by the ascomycetes Talaromyces marneffei in Candida albicans ATCC 10231, C. tropicalis ATCC 1369, Escherichia coli ATCC 25922 and Staphylococcus aureus ATCC 25923, and cytotoxic activity in vitro against strains of tumor cells (MCF-7) and normal cells (GM07492). Methodology: Broth microdilution techniques were used to analyze the antimicrobial activity. For analysis of the cytotoxic activity the MTT assay was used [3- (4,5-dimethylthiazol-2-yl) -2,5-diphenyltetrazolium bromide]. Results: Minimum bactericidal concentration (MBC) of T. marneffei’s IRPE for E. coli ATCC 25922 and S. aureus ATCC 25923 was 1000 μg/ml. The minimum inhibitory concentrations (MIC) for E. coli were 250 and for S. aureus 500 μg / mL, whereas for C. tropicalis ATCC 1369 it was 62.5 μg/mL. Half of the maximal inhibitory concentration (IC50) for breast cancer cell line (MCF-7) was 45.43 ± 1.657 μg / mL, however, no cytotoxicity was observed in the normal cell line tested (GM07492). Therefore, IRPE from T. marneffei showed intermediary antimicrobial and cytotoxic activities in vitro for the microorganisms and tumor cell line tested, and did not present cytotoxicity to the normal cells tested. It is suggested to carry out the isolation of the bioactive substances present in the extract in order to obtain more promising biological activities.